58. Repetitive transcranial magnetic stimulation induces neuroprotection via activating CaMKIIα-CREB-Bcl-2 pathway in rat brain. Issue 4 (April 2016) - Terranova, C.; Rizzo, V.; Rajan, T.S.; Naro, A.; Ahmad, A.; Ghilardi, M.F.; Bruschetta, D.; Girlanda, P.; Cuzzocrea, S.; Wang, H.Y.; Quartarone, A.
Abstract : Repetitive transcranial magnetic stimulation (rTMS) affects neuronal plasticity in humans and animals, even if the molecular mechanisms underlying rTMS effects are still not clear. In this study we examined whether low and high frequency rTMS may be neuroprotective. To achieve this aim, we determined Bcl-2/Bax expression in the prefrontal cortex of rats treated with 1 Hz or 5 Hz rTMS for five consecutive days. In addition, we examined CaMKII α and CREB brain plasticity related proteins and their role in regulating Bcl-2/Bax. We found that both 1 Hz and 5 Hz rTMS increase Bcl-2, CaMKII α and CREB expression. Our results suggest that both 1 and 5 Hz rTMS treatment for 5 days may produce neuroprotective effects by increasing expression of neuroprotective Bcl-2. This rTMS- induced Bcl-2 synthesis is likely mediated by the heightened activation and expression of CaMKII α - and CREB.